Diagnosis, management and response criteria of iron overload in myelodysplastic syndromes (MDS): updated recommendations of the Austrian MDS platform. Issue 2 (1st February 2018) - Valent, Peter; Stauder, Reinhard; Theurl, Igor; Geissler, Klaus; Sliwa, Thamer; Sperr, Wolfgang R.; Bettelheim, Peter; Sill, Heinz; Pfeilstöcker, Michael
ABSTRACT: Introduction : Despite the availability of effective iron chelators, transfusion-related morbidity is still a challenge in chronically transfused patients with myelodysplastic syndromes (MDS). In these patients, transfusion-induced iron overload may lead to organ dysfunction or even organ failure. In addition, iron overload is associated with reduced overall survival in MDS. Areas covered : During the past 10 years, various guidelines for the management of MDS patients with iron overload have been proposed. In the present article, we provide our updated recommendations for the diagnosis, prevention and therapy of iron overload in MDS. In addition, we propose refined treatment response criteria. As in 2006 and 2007, recommendations were discussed and formulated by participants of our Austrian MDS platform in a series of meetings in 2016 and 2017. Expert commentary : Our updated recommendations should support early recognition of iron overload, optimal patient management and the measurement of clinical responses to chelation treatment in daily practice.